Thermal regimes and horizontal surface velocities on Hellstugubreen and Storbreen, Jotunheimen, Southern Norway - Tachon, Mathieu (2015)
Radio-Echo Sounding (RES) surveys are an effective way to map the thermal regime of glaciers. RES measurements at two different center frequencies were conducted on Hellstugubreen and Storbreen, two mountain glaciers located in Jotunheimen, Southern Norway. The ice thickness was investigated from measurements at a frequency of 10 MHz, from 2011 at Hellstugubreen and from 2005-2006 at Storbreen. In 2014, RES surveys at a frequency of 50 MHz was used to map the internal thermal layering of the glaciers. Ice temperature variations in the subsurface were also explored with shallow borehole measurements. The results revealed a polythermal regime for both glaciers, which are cold-based near the front and their margins, and with a cold surface layer underlain by temperate ice in their central parts. A maximum ice thickness of 177 m (+-15 m) was recorded at Hellstugubreen. The bedrock was encountered at a maximum depth of 233 m (+-15 m) at Storbreen (uncorrected for the surface lowering of the past 10 years). The depth of the Cold-temperate Transition Surface (CTS) generally increased with elevation, and reached a maximum depth of 90 m at Hellstugubreen and 55 m at Storbreen. By the end of the summer season, remaining cold ice was found in the subsurface of Hellstugubreen,whereas on Storbreen, the cold wave was completely eliminated at same depth levels. Stake surveys based on accurate Differential Global Navigation Satellite System (DGNSS) georeferencing were carried out since September 2009 on Hellstugubreen and since September 2006 on Storbreen. The data available were exploited to gain an insight into the surface velocities of both glaciers. For the period 2013-2014, the surface velocities ranges from 0.5 m.yr -1 to 15.8 m.yr-1 at Hellstugubreen. Between 2010 and 2014, the measurements at Storbreen indicated surface velocities ranging from 2.5 m.yr-1 up to 16.2 m.yr-1.